2017
DOI: 10.1111/jop.12581
|View full text |Cite
|
Sign up to set email alerts
|

Oral submucous fibrosis: An update on current theories of pathogenesis

Abstract: Over the last 40 years, many theories linking oral submucous fibrosis (OSMF) to various risk factors have been proposed. Spicy, pungent foods and irritants such as supari (areca nut), paan (betel leaves), tobacco (through chewing or smoking)-the common Asian habits of chewing the aforementioned agents-have all been incriminated as causative agents. Systemic factors such as nutritional deficiency, genetic predisposition and autoimmunity have also been proposed in the pathogenesis of OSMF. However, the precise a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 27 publications
0
64
0
Order By: Relevance
“…COL I and III were the main collagen types in OSF. It was evident that there was a 1.5‐fold increase in collagen production in OSF fibroblasts with a ratio of type I to type III collagens similar to normal fibroblasts (Arakeri et al, ). In this present study, we indicated that upregulation of miR‐199‐5p could increase expression of COL I and III, whereas its downregulation exerted opposite actions.…”
Section: Discussionmentioning
confidence: 99%
“…COL I and III were the main collagen types in OSF. It was evident that there was a 1.5‐fold increase in collagen production in OSF fibroblasts with a ratio of type I to type III collagens similar to normal fibroblasts (Arakeri et al, ). In this present study, we indicated that upregulation of miR‐199‐5p could increase expression of COL I and III, whereas its downregulation exerted opposite actions.…”
Section: Discussionmentioning
confidence: 99%
“…Oral submucous fibrosis (OSMF) is a chronic, debilitating condition of the oral cavity causing progressive scarring of the oral mucosa . There has been recent discussion regarding the classification and staging of OSMF .…”
Section: Introductionmentioning
confidence: 99%
“…Research on the senescence of oral submucous fibroblasts has informed us about a relationship between senescence and oral submucous fibrosis (OSMF) in humans. OSMF is positively correlated with the incidence of oral cancer (Jayanthi, Probert, Sher, & Mayberry, 1992) and is no longer found only in Asia (Arakeri et al, 2017). An imbalance of collagen metabolism in the oral mucosa after chronic exposure to irritants such as areca nut and tobacco is considered to be one of the main pathological causes of OSMF (Arakeri et al, 2017).…”
Section: Effect Of Myofibroblast Senescence On Oral Submucous Fibrosismentioning
confidence: 99%
“…OSMF is positively correlated with the incidence of oral cancer (Jayanthi, Probert, Sher, & Mayberry, 1992) and is no longer found only in Asia (Arakeri et al, 2017). An imbalance of collagen metabolism in the oral mucosa after chronic exposure to irritants such as areca nut and tobacco is considered to be one of the main pathological causes of OSMF (Arakeri et al, 2017). Through biopsy of OSMF, senescent fibroblasts were found to accumulate as the disease progressed and oxidative stress may be a major triggering factor.…”
Section: Effect Of Myofibroblast Senescence On Oral Submucous Fibrosismentioning
confidence: 99%